A Phase I Clinical Study of High-Dose Ketoconazole Plus Weekly Docetaxel in Metastatic Castration-Resistant Prostate Cancer - Figg, William D. (2010)
PURPOSE: High-dose ketoconazole and docetaxel have shown activity as single agents against castration-resistant prostate cancer (CRPC). The goal of this phase I study was to determine the maximum tolerated doses, side effects, and pharmacokinetic interaction of coadministered docetaxel and ketoconazole. EXPERIMENTAL DESIGN: Patients with metastatic CRPC received weekly docetaxel for 3 of every 4 weeks, plus daily ketoconazole. Pharmacokinetic studies were performed on day 1 (docetaxel alone) and day 16 (after ketoconazole). RESULTS: The study enrolled 42 patients at 9 different dose levels. The combination regimens investigated included docetaxel weekly for three weeks out of four escalating from 5 to 43 mg/m(2), with starting doses of ketoconazole of 600, 800, or 1200 mg/day. Declines in prostate-specific antigen of ≥ 50% were seen in 62% of patients. Of 25 patients with soft tissue disease, 7 (28%) had partial response. Median overall survival was 22.8 months, and was significantly greater in docetaxel-naïve patients than in patients pretreated with docetaxel (36.8 vs. 10.3 months; P = 0.0001). The most frequently observed adverse events were anemia, edema, fatigue, diarrhea, nausea, sensory neuropathy, and elevated liver function tests. The fractional change in docetaxel clearance correlated significantly with ketoconazole exposure (P < 0.01). Concomitant ketoconazole increased docetaxel exposure 2.6-fold with 1200 mg/day, 1.6-fold with 800 mg/day, and 1.3- to 1.5-fold with 600 mg/day. CONCLUSIONS: Results suggest that the combination of weekly docetaxel and ketoconazole has significant antitumor activity in CRPC with manageable toxicities. The extremely long survival in the docetaxel-naïve cohort (36.8 months) warrants additional larger trials of docetaxel with ketoconazole or possibly CYP17A1 inhibitors such as abiraterone.